PENYATUATAPAN PERADILAN AGAMA (SUATU PERSPEKTIF DINAMIKA SEJARAH) - Abd Khalik Latuconsina (TAHKIM, 2017)
Religious Courts, as well as the judiciary, the New Order era was on two roofs, or power (judicial and executive). But after adannya Act No. 5 of 2004, concerning Amendment to Law No. 14 Year 1985 regarding the Supreme Court, the Religious Courts have under one roof, namely the Supreme Court. It was in accordance with Law No. 3 of 2006 on amendments to the Law No. 7 of 1989 on Religious Courts. Through this latest legislation, the Religious Courts the authority to examine the dispute in the field of Islamic economics. Keywords: putting, the judiciary religious, historical dynamics